Exercise-induced metabolic acidosis: Where do the protons come from? - Robergs, R. A. (Sportscience, 2001)
The widespread belief that intense exercise causes the production of "lactic acid" that contributes to acidosis is erroneous. In the breakdown of a glucose molecule to 2 pyruvate molecules, three reactions release a total of four protons, and one reaction consumes two protons. The conversion of 2 pyruvate to 2 lactate by lactate dehydrogenase (LDH) also consumes two protons. Thus lactate production retards rather than contributes to acidosis. Proton release also occurs during ATP hydrolysis. In the transition to a higher exercise intensity, the rate of ATP hydrolysis is not matched by the transport of protons, inorganic phosphate and ADP into the mitochondria. Consequently, there is an increasing dependence on ATP supplied by glycolysis. Under these conditions, there is a greater rate of cytosolic proton release from glycolysis and ATP hydrolysis, the cell buffering capacity is eventually exceeded, and acidosis develops. Lactate production increases due to the favorable bioenergetics for the LDH reaction. Lactate production is therefore a consequence rather than a cause of cellular conditions that cause acidosis. Researchers, clinicians, and sports coaches need to recognize the true causes of acidosis so that more valid approaches can be developed to diminish the detrimental effects of acidosis on their subject/patient/client populations.